RECONSTRUCTING ISLAMIC EDUCATION PEDAGOGY IN THE DIGITAL AGE: INTEGRATING SPIRITUAL ETHICS AND DIGITAL LITERACY - Miftahussurur, Wildan (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2026)
This study aims to reconstruct Islamic Religious Education (PAI) pedagogy in the digital age through the integration of spiritual ethics and digital literacy. The rapid advancement of digital technology has significantly transformed educational practices, challenging conventional PAI pedagogy that remains largely teacher-centered, text-oriented, and less responsive to contemporary learning demands. This condition has led to a gap between cognitive understanding of religious teachings and their practical application in real-life and digital contexts. This research employs a qualitative approach using a conceptual and library-based method, drawing upon classical Islamic scholarship and contemporary theories of digital pedagogy. Data were collected through a systematic literature review and analyzed using thematic and integrative approaches to develop a comprehensive pedagogical framework. The findings reveal that the reconstruction of PAI pedagogy requires a balanced integration between spiritual ethics and digital literacy. Spiritual ethics function as a moral foundation that guides learners’ behavior and decision-making, while digital literacy equips them with the skills to critically and responsibly engage with digital environments. The study proposes a conceptual model termed Spiritual-Digital Integrative Pedagogy, which emphasizes ethical orientation, critical digital engagement, and reflective learning as its core components. This study contributes to the development of Islamic education by offering a new integrative paradigm that bridges tradition and modernity. It also provides practical implications for educators and policymakers in designing value-based digital learning environments.